Use of mineral licks by mammals in areas of the Amazonia with no hunting pressure - Macas-Pogo, Patricio; Osorio Sánchez, María Cristina (THERYA, 2021)
Mineral licks are areas where several species of animals, including mammals, converge to consume water and soil as a mineral supplement. Certain mammal species are an important source of protein in the diet of indigenous communities. Many of these species are under hunting pressure and their populations have been seriously affected. The purpose of this study was to determine the species of large and medium-sized mammals that use three open mineral licks in the area of the Kichwa Añangu community, within the Yasuní National Park, where hunting used to take place. We calculate the capture frequency for the visiting species and the richness, composition, and similarity of the assemblages recorded in the mineral licks during two climatic seasons of the year (higher rainfall vs. lower rainfall). We installed a single camera trap station (CTS) at each mineral lick during three sampling periods in 2018. In each period, all cameras operated 24 hours a day for 30 to 40 days and were set to capture three photographs upon sensor activation, with 60-second intervals between consecutive activations. With a total sampling effort of 249 days/trap, we obtained 645 photographs and 398 grouped records of 16 species. We recorded 95.2 % of the expected richness according to the Chao1 estimator (S = 16.8). The species with the highest capture frequency were: Mazama zamora (FC = 62.2), Tayassu pecari (FC = 35.7), Tapirus terrestris (FC = 28.9), and Pecari tajacu (FC = 8.0). ECT-1 and ECT-2 captured 11 species each, and ECT-3 captured nine species. There were no significant differences in the species composition between the three mineral licks or between climatic seasons. Our results show that the focal mineral licks studied attract a rich mammalian fauna, which likely points to the success of the government regulation of wildlife trafficking and the application of sustainable tourism practices in the Añangu community.